# Find the remainder when f(x) is divided by (x - k); f(x) = 3x^{4} + 11x^{3} + 2x^{2} - 7x + 61; k = 3.

**Solution:**

We will use the remainder theorem to find the remainder.

f(x) = 3x^{4} + 11x^{3} + 2x^{2} - 7x + 61 is divided by (x - k)

⇒ x = k where value of k = 3 (given)

Substitute the value of x = k = 3 in the equation.

f(k = 3) = 3(3)^{4} + 11(3)^{3} + 2(3)^{2} - 7(3) + 61

f(k) = 243 + 297 + 18 - 21 + 61

f(k) = 598

## Find the remainder when f(x) is divided by (x - k); f(x) = 3x^{4} + 11x^{3} + 2x^{2} - 7x + 61; k = 3.

**Summary:**

Therefore, the remainder when f(x) = 3x^{4} + 11x^{3} + 2x^{2} - 7x + 61is divided by (x - k); k = 3 is 598.